2014
DOI: 10.1063/1.4903906
|View full text |Cite
|
Sign up to set email alerts
|

Filamentary structure of plasma produced by compression of puffing deuterium by deuterium or neon plasma sheath on plasma-focus discharge

Abstract: The present experiments were performed on the PF-1000 plasma focus device at a current of 2 MA with the deuterium injected from the gas-puff placed in the axis of the anode face. The XUV frames showed, in contrast with the interferograms, the fine structure: filaments and spots up to 1 mm diameter. In the deuterium filling, the short filaments are registered mainly in the region of the internal plasmoidal structures and their number correlates with the intensity of neutron production. The longer filamentary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The diameter of the pinholes was 80 m and the magnifi cation ratio was equal to 10. Therefore, the spatial inaccuracy of the gained frames was about 0.8 mm [1,2]. The angle between the optical axis of the MCP detector and the main interferometric beam was 45°.…”
Section: Experimental Arrangementmentioning
confidence: 99%
See 4 more Smart Citations
“…The diameter of the pinholes was 80 m and the magnifi cation ratio was equal to 10. Therefore, the spatial inaccuracy of the gained frames was about 0.8 mm [1,2]. The angle between the optical axis of the MCP detector and the main interferometric beam was 45°.…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…The short description of the ball-like structures observed in shot #10080 and #10122 was presented in a paper [1]. In that paper, it was observed that the ball-like structures occurred at the imploding plasma shell boundary, the lifetime of the structures could be longer than 200 ns, the maximum electron density in the center of such structures was about 10 25 m -3 .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations